2015
DOI: 10.1016/j.bbamcr.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of β-barrel proteins in the mitochondrial outer membrane

Abstract: Mitochondria evolved through endosymbiosis of a Gram-negative progenitor with a host cell to generate eukaryotes. Therefore, the outer membrane of mitochondria and Gram-negative bacteria contain pore proteins with β-barrel topology. After synthesis in the cytosol, β-barrel precursor proteins are first transported into the mitochondrial intermembrane space. Folding and membrane integration of β-barrel proteins depend on the mitochondrial sorting and assembly machinery (SAM) located in the outer membrane, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 274 publications
0
63
0
Order By: Relevance
“…The overexpression of these proteins reverted the globular mitochondrial morphology of mdm10 ERMES core complex, Mdm10, is a mitochondrial -barrel protein. Mdm10 is also part of another complex, sorting and assembly machinery (SAM), required for the assembly of -barrel proteins in the outer mitochondrial membrane (75,90). Because Mdm10 seems to be present in limiting amount, the availability of Mdm10 for assembling into those different complexes might play a regulatory role.…”
Section: Mitochondrial Connections Beyond Ermesmentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of these proteins reverted the globular mitochondrial morphology of mdm10 ERMES core complex, Mdm10, is a mitochondrial -barrel protein. Mdm10 is also part of another complex, sorting and assembly machinery (SAM), required for the assembly of -barrel proteins in the outer mitochondrial membrane (75,90). Because Mdm10 seems to be present in limiting amount, the availability of Mdm10 for assembling into those different complexes might play a regulatory role.…”
Section: Mitochondrial Connections Beyond Ermesmentioning
confidence: 99%
“…Mitochondria are organelles of endosymbiotic origin that, over evolution, have transferred most of their protein encoding genes into the cell host nucleus, with only a few genes still residing in the mitochondrial DNA (mtDNA) (71). Dedicated mitochondrial machineries allow for the import, folding, and assembly of the nuclear-encoded proteins required for proper mitochondrial physiology (72)(73)(74)(75). Mitochondria are also equipped with a family of carriers that facilitate the transport of small soluble molecules like amino acids, nucleotides, and vitamins across the mitochondrial inner membrane, necessary for the interdependent metabolism at both sides of the mitochondrial double membrane (76,77).…”
Section: Making Mitochondrial Membranes: the Contribution Of Er-mitocmentioning
confidence: 99%
“…The core component Mia40 recognizes the precursor proteins and mediates the formation of disulfide bonds in the imported proteins. (iv) The precursors of β-barrel proteins of the outer membrane are translocated through the TOM channel to the small TIM chaperones and are inserted into the outer membrane by the sorting and assembly machinery (SAM, also termed TOB complex) (Walther and Rapaport, 2009;Höhr et al, 2015).…”
Section: Principles Of Mitochondrial Protein Importmentioning
confidence: 99%
“…Metaxins have been identified more recently as members of the Sorting and Assembly Machinery (SAM) (13,14) which facilitate the membrane insertion of beta-barrel proteins family which include VDAC (Höhr et al, 2015). Mtx1 has been shown to be required for the TNF-induced cell death (15) and that its deficiency led to mitochondrial anti-apoptotic phenotypes (16).…”
Section: Introductionmentioning
confidence: 99%
“…Metaxins have been identified more recently as members of the Sorting and Assembly Machinery (SAM) (13,14) which facilitate the membrane insertion of beta-barrel proteins family which include VDAC (Höhr et al, 2015). Mtx1 has been shown to be required for the TNF-induced cell death (15) and that its deficiency led to mitochondrial anti-apoptotic phenotypes (16). Recently, we have shown that Bak interacted with Mtx2 in resting cells and with Mtx1 upon TNF treatment (6) The role and the regulation of apoptosis by the different mitochondrial receptors of the Bcl-2 family are not completely understood and it has been speculated that it could affect cell death only under specific physiological situations (17,18).…”
Section: Introductionmentioning
confidence: 99%